EFFECT OF PANDANUS AMARYLLIFOLIUS FIBRE ON PHYSIO-MECHANICAL, THERMAL AND BIODEGRADABILITY OF THERMOPLASTIC CASSAVA STARCH/BEESWAX COMPOSITES - ZAKUAN, NUR DIYANA; Jumaidin, Ridhwan; Selamat, Mohd Zulkefli; Mohd Suan, Mohd Shahadan; Hazrati, K. Z.; Md Yusof, Fahmi Asyadi; Ilyas, R. A.; Eldin, Sayed M. (Springer, 2023)
Pandanus amaryllifolius fbre (PAF) is an agricultural waste plant derived from the natural cellulosic source of fbre that can be used in various bio-material applications. In the present study, a novel biodegradable thermoplastic cassava starch/beeswax blends reinforced with Pandanus amaryllifolius fbre (TCPS/BW/PAF) bio-composites were successfully developed at varied Pandanus amaryllifolius fbre concentrations of 0, 10, 20, 30, 40, 50 and 60 wt% while beeswax loading was remained constant at 2.5 wt% concentration using hot moulding compression method. A comprehensive characterisation of TCPS/ BW/PAF bio-composites was examined in terms of their physical, mechanical, thermal and biodegradation properties. The addition of Pandanus amaryllifolius fbre has signifcantly improved tensile strength and tensile modulus at maximum value obtained 10.9 and 606.5 MPa, respectively as well as fexural strength and fexural modulus of bio-composite at maximum value obtained 21.37 and 523.76 MPa, respectively until 50 wt% Pandanus amaryllifolius fbre loading. Surface morphology of the fractured tensile samples PAF10 to PAF50 shows compacted structure and fbre breakage, indicating efective stress transfer from starch matrix to PAF during tensile force application. Furthermore, the addition of Pandanus amaryllifolius fbre improved thermal stability from TG, DTG and DSC results; improved crystallinity from XRD analysis; reduced water and moisture afnity from physical properties testing, and lowered the biodegradation rate. Overall, this study shows the potential of TCPS/BW/PAF bio-composites in biopolymer application and bio-packaging industries.